근로자 정기건강검진을 기초로 한 영양 및 건강관리 전산화 프로그램 개발에 관한 연구 - 노성윤; 조여원 (Korean journal of community nutrition, 2002)
In this study, a computerized nutritional and health guide program for workers was developed. The dietitian at the work site could utilize periodically conducted medical examination data to develop an effective health care counseling model based on the developed Nutritional and Health Guide Program. A personal computer (Pentium II PC MMX-150, 32MB RAM, 2.95 GB HDD) with Microsoft Visual Basic 6.0 Enterprise Edition and Microsoft Access 97 installed, was used. The Nutritional and Health Guide Program consisted of seven main menus and 43 sub-menus. Included in the main menu were Basic Information, Periodic Health Check-ups, Visitors' Consultations, Nutritional/Health Tips, Nutritional Education according to Diseases, Help and Exit. In the Periodic Health Check-up menu, dieticians could input the health examination data of employees and touch for the recommended treatments for diseases such as obesity, diabetes, high cholesterol, hypertension and hepatitis. The Visitors'Consultation menu has been designed to compile health information about the employees who sought consultations. The Nutritional/Health Tips menu was designed to provide 14 kinds of programmed nutritional educational media and information. In the Nutritional Education According to Diseases menu, the dietitian could judge the subject's willingness to obtain treatment based on the Stage of Change Model. According, the content of the administered respective nutritional education was classified by stages. The Help menu, provide a chart of the method and procedure used as nutritional guidelines, by which the results of the health examination were classified as people in good health and those requiring special medical attention. The results of the evaluation of this program showed highly positive rates for usefulness (4.09), convenience (4.04), lettering size (4.02), interest (3.93), design (3.49). It also showed that 97.5% of the subjects thought that this program would be helpful for implementation of their company's nutritional educational program. Therefore, this menu could help dietitians plan, conduct, and evaluate their nutritional guidelines for employees. It is expected that The Nutritional and Health Guide Program developed in this study will play a role as a scientific and effective guide in conjunction with health examination results.